Design, synthesis, in vitro, and in silico studies of 4-fluorocinnamaldehyde based thiosemicarbazones as urease inhibitors - Muhammad Islam; Saeed Ullah; Ajmal Khan; Zahra Batool; Suraj N. Mali; Shailesh S. Gurav; Kholood A. Dahlous; Saikh Mohammad; Javid Hussain; Ahmed Al-Harrasi; Zahid Shafiq (Scientific Reports)
Abstract Clinically significant problems such as kidney stones and stomach ulcers are linked to the activation of the urease enzyme. At low pH, this enzyme gives an ideal environment to Helicobacter pylori in the stomach which is the cause of gastric ulcers and peptic ulcers. In recent work, we have developed a library of 4-fluorocinnamaldehyde base thiosemicarbazones and assessed them for their potential against urease enzyme. The synthesized compounds displayed significant to moderate inhibition potential with IC50 values ranging from 2.7 ± 0.5 µM to 29.0 ± 0.5 µM. compound 3c displayed the highest inhibition potential followed by 3a and 3b. Two compounds of the series 3f and 3 g remained inactive against urease. The kinetic study of compound 3c exhibited a competitive type of inhibition with a K i value of 3.26 ± 0.0048 µM. SAR analysis was also thoroughly done. Molecular docking was used to analyze the interaction pattern of each derivative, and the outcomes demonstrated that the compounds had excellent binding interactions with the active site.